2012
DOI: 10.1002/pon.3054
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception clusters at diagnosis predict psychological distress among women with breast cancer at 6 months post diagnosis

Abstract: Objective: This study aimed to examine the extent to which illness perceptions and coping strategies among women diagnosed with breast cancer explain psychological distress at diagnosis and at six months post-diagnosis relative to demographic and illness-related variables. Methods: Women were recruited to the study shortly after diagnosis. A total of 90 women completed study materials (Illness Perception Questionnaire-Revised, the Cancer Coping Questionnaire and the Hospital Anxiety and Depression Scale) at ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
6
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 29 publications
6
100
6
3
Order By: Relevance
“…Several previous studies have shown that increased use of approach-coping methods was related to positive outcomes, whereas avoidant coping was related to a greater number of negative outcomes. [102122] In the present study, there was no remarkable use regarding escape-avoidance and distancing, namely avoidant coping methods.…”
Section: Discussioncontrasting
confidence: 48%
“…Several previous studies have shown that increased use of approach-coping methods was related to positive outcomes, whereas avoidant coping was related to a greater number of negative outcomes. [102122] In the present study, there was no remarkable use regarding escape-avoidance and distancing, namely avoidant coping methods.…”
Section: Discussioncontrasting
confidence: 48%
“…These representations relate to thoughts about, for example, the causes of the illness, worries and fears, the ability to control the illness, and accepting the illness [12] and can be maladaptive as well as adaptive in terms of outcome [9] and some are typically more adaptive than others. These representations have been investigated using terms such as illness cognitions, illness perceptions, illness representations and appraisals.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, timeline, identity, consequences, and attributing psychological causes for the illness predicted both stress and depressive symptoms, with treatment control and coherence also accounting for a significant proportion of the variance in stress. Additional studies have linked dimensions of emotional representation, consequences, control, identity, and timeline to depressive symptoms (Gray et al, 2015; McCorry et al, 2013; Silva, Moreira, & Canavarro, 2012; Dempster et al, 2011). Finally, despite the common occurrence of cancer-related fatigue, we were able to locate only one study documenting its relation to illness perceptions.…”
Section: Introductionmentioning
confidence: 99%